Tinjauan Umum Yuridis Teoritis Peranan Regulator Jasa Keuangan Atas Penerapan Prinsip Prudential Banking Terhadap Produk Peer To Peer Lending Pada Aplikasi Financial Technology Dalam Rangka Perlindungan Hukum Pemberi Pinjaman (Kreditur) Dan Penerima Pinjaman (Debitur) - Fontian Munzil (Jurnal Media Justitia Nusantara, 2018)
The national vision of financial inclusive has been formulated in order to realize a financial system that can be accessed by all levels of society with the aim of encouraging national economic growth in the micro and small enterprises segment. The implementation of digital financial services, namely financial technology with peer to peer lending features is a form of information technology-based money lending services. The author will conduct research, first, how is the application of the principle of prudential banking to peer to peer lending products on the application of financial technology? second, how far can the role of the financial services regulator reach the legal protection of creditors debtors for the delivery of peer to peer lending services in the application of financial technolog? This study uses a normative juridical approach in accordance with the field of legal studies. Assessment is carried out on legal principles which are the research of philosophical aspects because the legal principle is an ideal element of law and legal norms contained in the laws and regulations. The data collection technique is library research to collect problem references as well as legislation according to the problem being studied. Data obtained from secondary data using primary, secondary and tertiary legal materials. The research specification is descriptive analysis to provide data as accurately as possible and all data collected has been analyzed qualitatively juridically and described analytically descriptively. The study found that, first, the application of the prudential banking principle of peer to peer lending products in the application of financial technology was not optimal, second, regulators have not optimally regulated the relationship of asymmetry between lenders and loan recipients, the amount of loan interest rates, guarantee of non-performing loans, confidentiality of loan recipient data related to collection of non-performing loans, track record of loan recipients, suspicious transaction reporting for financial technology business entities and status/form of financial technology business entity including portion of ownership by foreign parties in financial technology lending providers.